153 AN EVALUATION OF OLDER PERSONS WITH VESTIBULAR DYSFUNCTION AS IDENTIFIED DURING COMPREHENSIVE GERIATRIC ASSESSMENT. (25th October 2022) - Sayers, K; Treacy, G; King, L; Ryan, S; Donnellan, C
Abstract: Background: Vestibular dysfunction accounts for 25% of dizziness complaints. In 30-50% of these cases, dizziness is attributed to Benign Paroxysmal Positional Vertigo (BPPV). Thirty percent of people will experience vestibular dysfunction in their lifetime, with likelihood increasing with age. Individuals with vestibular dysfunction are eight times more likely to experience a fall. Vestibular assessment and rehabilitation services can be difficult to access. Methods: A Plan, Do, Study, Act (PDSA) cycle was undertaken. All referrals to the Older Persons' Services Clinics from November 2021 to May 2022 were triaged by an Integrated Care Team for the Older Person and scheduled for Comprehensive Geriatric Assessment (CGA). In the course of CGA, patients who reported symptoms suggestive of vestibular dysfunction received assessment by a Physiotherapist with vestibular expertise. Results were entered on an Excel spreadsheet and analysed using descriptive statistics. Results: Six patients (4 female, 2 male) received vestibular assessment and treatment. Mean age was 75 years (SD: 11) with median Clinical Frailty Score of 4 (vulnerable). Reported symptoms were dizziness (n=3) and spinning (n=3). Sixteen percent (n=1) reported a fall and 66% (n=4) reported fear of falling. All patients had symptom duration of >2 years. Following vestibular assessment, the following diagnoses were made; right posterior canal BPPV, (n=2), vestibular migraine (n=2), right horizontal canal canalithiasis BPPV, with secondary diagnosis of persistent postural-perceptual dizziness (n=1) and left peripheral vestibular hypofunction due to vestibular neuronitis (n=1). The mean number of Physiotherapy visits per person was 4. Three patients reported full resolution of symptoms. The remaining 3 reported an improvement in symptoms and confidence to self-manage. Conclusion: This small cohort of older persons with chronic vestibular dysfunction benefited from vestibular diagnosis and intervention. The next step of the process is to include specific vestibular screening questions into CGA. This will enable Integrated Care Team members to screen more specifically for vestibular dysfunction.